(untitled) (Bangladesh Journal of Medicine, 2015)
Introduction: Liver abscess is an important clinical problem in tropical regions of the world. Current assessment of liver abscesses should allow for better understanding of the aetiopathogenesis of the disease. This study was conducted to find the clinical pattern and aetiopathogenesis of liver abscess in patients admitted in Rajshahi Medical College Hospital. Methodology: The present cross-sectional study was carried out in the Department of Medicine, Rajshahi Medical College Hospital (RMCH) on consecutive 34 patients of liver abscess admitted between the period of July 2002 and June 2003. Detailed history and clinical examination were performed in all patients. All routine investigations were done. Liver abscess was confirmed by ultrasonography (USG). Aspiration of liver abscess was done under sonographic guidance in the Nuclear Medicine Department of RMCH to diagnose the cause of liver abscess. Aspirated materials were sent for microscopical examination and culture and sensitivity in the Department of Microbiology of the same Institute. Result: The findings showed that early middle-aged population were usually affected by liver abscess followed by middle aged (mean age around 40 years). The patients were predominantly male with males being 16 times more likely to suffer from the disease than the females. Most of the patients belong to low socioeconomic status (82.4%). All patients had fever and malaise. Other common manifestations were loss of appetite, lump in the abdomen, intercostal tenderness, nausea/ vomiting, loss of weight. Less common presentations were diarrhoea (29.4%), jaundice (23.5%), cough (11.8%), chest pain (11.8%) and breathlessness (2.9%). Liver span of the patients measured by ultra-sonogram showed hepatomegaly in all cases. All patients with pyogenic liver abscess and 75% of the patients with amoebic abscess had the history of prolonged intake of fermented palm juice (palm wine). Microscopic examination of the pus/aspirate drawn from the liver revealed trophozoite in 7(20.6%) cases. However, on culture of the specimen, 12(35.3%) were culture positive and 22(64.7%) were culture negative. Conclusion: Middle-aged male with low socioeconomic status with the history of prolonged palm wine intake are the most common characteristic of patients with liver abscess. Multi-center study with large sample size is recommended to verify the findings of the present study. Bangladesh J Medicine Jul 2015; 26 (2) : 55-60